2017
DOI: 10.1186/s12891-017-1438-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic change of nerve and symptom relief are similar after mini-incision and endoscopic carpal tunnel release: a randomized trial

Abstract: BackgroundThe symptoms in carpal tunnel syndrome (CTS) can be ameliorated by open and endoscopic release of the transverse carpal ligament. It is unknown whether a mini-incision or endoscopic carpal tunnel release more effectively reverses the pathological changes that are observed in the median nerve in patients with CTS and these morphologic changes correlates with the subjective outcomes after carpal tunnel release. We hypothesized that (1) at 24 weeks after surgery, the subjective outcomes of mini-incision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
1
18
1
1
Order By: Relevance
“…Kim et al found no correlation between proximal CSA changes and BCTQ changes after open CTR. Oh et al found a significant correlation between a reduced proximal CSA and improved BCTQ‐SS scores after open/endoscopic CTR ( r = 0.38). Tran et al observed a strong correlation ( r = 0.61) between a reduced proximal CSA and improved BCTQ‐FS scores after open CTR but only a weak correlation with improved BCTQ‐SS scores ( r = 0.26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kim et al found no correlation between proximal CSA changes and BCTQ changes after open CTR. Oh et al found a significant correlation between a reduced proximal CSA and improved BCTQ‐SS scores after open/endoscopic CTR ( r = 0.38). Tran et al observed a strong correlation ( r = 0.61) between a reduced proximal CSA and improved BCTQ‐FS scores after open CTR but only a weak correlation with improved BCTQ‐SS scores ( r = 0.26).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have attempted to correlate clinical outcomes with changes in the nerve CSA after CTR, producing mixed results. 14,15,46,47 Although correlating changes in the nerve CSA with clinical outcomes was not a primary goal of our current investigation, we did attempt to identify correlations between median nerve CSA changes and BCTQ score changes. As shown in Table 4, there were no statistically significant correlations between nerve CSA changes and BCTQ score changes.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Although the standard carpal tunnel release has proven effective and safe, the limited method offer better appearance and minor wound complications compared with the standard open method. [12] Also, the limited technology provides an early return to activities, an early recovery of grip strength and pinch strength. [9] A meta-analysis with a large sample size may be necessary to detect such complications and differences in other outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have defined the outcomes of ECTR and OCTR as clinically equivalent for subjective symptom relief and morphologic changes of the median nerve and carpal canal. 9,12,17 Other studies have reported that ECTR is a superior method to OCTR, as endoscopic technique results in a shorter recovery time than OCTR. 3,18 As discussed previously, prior studies have been unable to obtain clearly reproducible results regarding the mechanism by which decompression of the median nerve occurs.…”
Section: Discussionmentioning
confidence: 99%